Synchronization protocols in distributed real-time systems - Sun, J.; Liu, J. (Proceedings of the 16th International Conference on Distributed Computing Systems, 1996)
In many distributed real-time systems, the workload can be modeled as a set of periodic tasks, each of which consists of a chain of subtasks executing on different processors. Synchronization protocols are used to govern the release of subtasks so that the precedence constraints among subtasks are satisfied and the schedulability of the resultant system is analyzable. Tasks have different worst-case and average end-to-end response times when different protocols are used. In this paper, we consider distributed real-time systems with independent, periodic tasks and fixed-priority scheduling algorithms. We propose three synchronization protocols and conduct simulation to compare their performance with respect to the two timing aspects.